Peran Sektor Publik dalam Akumulasi Human Capital dan Kapasitas Research & Development - Sanjoyo Sanjoyo (Jurnal Ketenagakerjaan, 2018)
Economic growth of a country is influenced by various factors, such as natural resources, capital, savings, and technological development. The wealth of natural resources will help a country's economy, but must be supported by natural resource exploration skills. Capital, savings and technology are the dominant elements of economic growth for the future. With technology allows manufacturers to produce more with the same input level. Technological development depends on the ability of science and the quality of education of a country and how much attention to research and development. The dynamic relationship between economic growth and human resources and research & development can be explained since 1980 when Romer and Lucas described the relationship with the growth model of endogenous or new growth theory. In this paper I will try to explain briefly the history of the economic development of growth theory and briefly review the core of the neoclassical model and the endogenous growth model. Then, this paper will explain the role of human capital accumulation and research & development in economic development. Finally, this paper will review the role of the public sector and policy implications in the process of human capital accumulation and research & development investment to contribute to economic growth.